Analisis Kemampuan Investigasi Matematik Materi Pola Bilangan Ditinjau Dari Perbedaan Jenis Kelamin Siswa Kelas IX SMPN 1 Mataram Tahun Ajaran 2021/2022 - Fela Nurma Alfianti; Sri Subarinah; Sudi Prayitno; Arjudin Arjudin (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to describe students' mathematical investigation abilities on number pattern material in terms of gender differences. This type of research is descriptive qualitative and quantitative with the instruments used in the form of mathematical investigation test questions, and interview guidelines. Subject selection using purposive sampling, which is based on the teacher's considerations. The subjects in this study were students of class IX-A of SMPN 1 Mataram for the academic year 2021/2022, totaling 32 students. The test results were analyzed for each item based on the ability of mathematical investigation including specializing, conjecturing, generalizing and justifying. The results showed that the mathematical investigation ability of female students as many as 10 students (62.5%) were able to work on the four stages, the three-stage category was 2 students (12.5%), the two-stage category was 3 students (18.75%), and one-stage category as many as 1 student (6.25%). While the mathematical investigation ability of male students as many as 8 students (50%) were able to work on all four stages, the three-stage category was 3 students (18.75%), the two-stage category was 5 students (31.25%). In this study, interviews were conducted with 6 students from each representative of each criterion of the mathematical investigation ability test results, namely 3 male students and 3 female students. The difference between male and female students lies in the generalizing and justifying stage where female students complete neatly, thoroughly and test the general pattern for the special case they are working on while the male students complete in a short way.